THE "FOOT" IN THE SCHOOL: THE APPRENTICESHIP IN THE INITIAL FORMATION OF THE PHYSICAL EDUCATION TEACHERS (Fiep Bulletin - online, 2011)
The objective of this study is to analyze and to discuss the difficulties presented by the students during the accomplishment of the first apprenticeship of the formation, that happens at the child school and in the initial years of the fundamental teaching. The need to accomplish such analysis elapses of some situations lived by a group of teachers, along a year of work, with students of the Course of Degree in physical education of the Federal University of Pelotas. We want in this writing to identify in the process of initial formation which work vision in the school permeates the projects of the students' educational exercise, as well as, to analyze which the perception of the formation and of the paper of the university in that process. This study followed the orientations of the qualitative methodologies of research (Triviños, 1992) that counted with a group of registrations in field diary for development accomplished by teachers of the Federal University of Pelotas along one school year. The study indicated arguments on the resistance of the students to the educational exercise as: the university is unstuck of the practice and of the reality; for the difficulties they should have solutions and ready answers; there is no planning need for the school work; it is not necessary to work collectively, because the solutions for the difficulties should be looked for individually. Besides, they still appear the specific subjects of the physical education, as if it was a space without learnings, of routines and of deliberated. That vision generates conflict for the academic that it is in the initial formation, since all that that he learns in the academical banks seems to have little or any meaning when it puts the " foot in the school
Keywords: formation; school; physical education